Un gesto atípico - Sakonoff, R.; Sakonoff, S.; Marcus, H.; Salazar, H.; Araoz, J.
Plazoleta San Miguel Arcangel implantada en el predio del Campus corporativo EDET.
Keywords: ARGENTINA; TUCUMAN; SAN MIGUEL DE TUCUMAN; PLAZOLETAS